1970
DOI: 10.1530/jrf.0.0210537
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Hypertrophy in Rats

Abstract: Experiments on hypertrophy of the testis have been carried out by Lipschutz (1922) who stated there was accelerated growth of the contralateral testis which rapidly reached maximum weight, but that no true hypertrophy occurred after unilateral orchidectomy. Grant (1955) stated that an increase in testicular volume occurred after unilateral orchidectomy in three albino rats. Shellabarger (1963) stated there was no increase in testicular weight after removal of a single testis. Being an endocrine organ, the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

1972
1972
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
3
2
Order By: Relevance
“…The results of volume fraction estimations of the testicular components showed that the hemicastrated testis contained more interstitial space, but there was no difference in the volume fraction of interstitial cells. This does not support the results of Liang and Liang (1970) who concluded that the increase in testicular weight after hemicastration was due in part to an increase in the interstitial cell number.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of volume fraction estimations of the testicular components showed that the hemicastrated testis contained more interstitial space, but there was no difference in the volume fraction of interstitial cells. This does not support the results of Liang and Liang (1970) who concluded that the increase in testicular weight after hemicastration was due in part to an increase in the interstitial cell number.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work reported an increase in the seminiferous tubule diameter of the contralateral testis after unilateral castration in the rat (Liang and Liang 1970), toad (Thyagaraja and Sarkar 1970), bull (Johnson 1978), and ram (Voglymayr and Mattner 1968;Johnson et al 1971). The present results also found that the area of the seminiferous tubule of hemicastrated rats was significantly larger than that of intact animals.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors concluded that the inferior spermatic nerve that runs along the ductus deferens and provides a minor supply of testicular innervation (Kuntz and Moris -1946;Hodson -1970) is involved in the testicular hemicastration response. However, in our study the compensatory hypertrophy that follows hemicastration (Lipschutz -1922;Liang and Liang -1970;Cunningham et al -1978;Orth et al -1984;Gerendai et al -1983) is not altered by vasectomy contralateral to the removed testis, a decrease in basal testosterone production can be observed. Since a similar decrease in basal testosterone production of the testes appears after bilateral vasectomy, it seems very likely that the decrease in steroid production in…”
Section: Discussioncontrasting
confidence: 60%
“…Perhaps the elevated LH levels are necessary to increase the number of interstitial cells in the remaining testis. Liang and Liang (6) found increased numbers of interstitial cells in testes of hemicastrated rats (LH levels presumably high) and decreased numbers in hemicastrates treated with testosterone cypionate (LH levels presumably low). Thus high LH levels may result in increased numbers of interstitial cells which, although not substantially increasing testis weight, might eventually be able to maintain normal rates of testosterone secretion without the necessity of con tinued high LH levels.…”
Section: Discussionmentioning
confidence: 99%